Identidad, género y trabajo en los estudios latinoamericanos - Luz Gabriela Arango Gaviria (Cahiers des Amériques Latines)
The article presents a partial assessment of the relationship between identity, gender and work in Latin America according to the sociology of Latin-American work, in particular, studies on gender and work. In spite of the recent development of studies on masculinity, the problem of female identity and the tension between family life and professional life, have occupied the place of choice amongst researchers. The article addresses the themes of masculinity and femininity in the professional space, changes between the generations in the construction of the identity of workers, the first results of studies on masculinity and finally, the new studies on unemployment, poverty and exclusion.